2018
DOI: 10.3892/mmr.2018.9773
|View full text |Cite
|
Sign up to set email alerts
|

MiR‑495 suppresses cell proliferation by directly targeting HMGA2 in lung cancer

Abstract: The present study aimed to investigate the expression of microRNA-495 (miR-495) in non-small cell lung cancer (NSCLC) tissues and cells, as well as its function on the proliferation of lung cancer cells. The expression of miR-495 in 122 pairs of NSCLC tissues and matched paracarcinoma tissues, as well as in human lung cancer cell lines (A549, H460, H1650, H520 and SK-MES-1) and the normal human pulmonary bronchial epithelial cell line 16HBE was determined using reverse transcription quantitative polymerase cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 41 publications
1
16
0
Order By: Relevance
“…Upregulated expression of miR-495 significantly downregulated the mRNA and protein expression levels of HMGA2 in A549 cells, and then suppressed the proliferation of lung cancer cells. 53 These above studies all indicated that miRNA is an important regulatory mechanism for the expression of HMGA2. It is reasonable to speculate that the rs8756 A>C in the 3ʹ UTR of the HMGA2 gene may affect some miRNA's binding to HMGA2, thereby alternating gene expression level.…”
Section: Discussionmentioning
confidence: 91%
“…Upregulated expression of miR-495 significantly downregulated the mRNA and protein expression levels of HMGA2 in A549 cells, and then suppressed the proliferation of lung cancer cells. 53 These above studies all indicated that miRNA is an important regulatory mechanism for the expression of HMGA2. It is reasonable to speculate that the rs8756 A>C in the 3ʹ UTR of the HMGA2 gene may affect some miRNA's binding to HMGA2, thereby alternating gene expression level.…”
Section: Discussionmentioning
confidence: 91%
“…HMGA2 is reported to be an oncogene that has been extensively studied in diverse tumors, such as colon, breast, and gastric cancer (Li et al, ;Mansoori et al, ;Sun, Qiao, Song, & Wang, ;Xi et al, ). HMGA2 can bind to the promoter of the cyclin gene, upregulates cyclin expression, accelerates the G2/M phase of the cell cycle, and enhances tumorigenesis (Fusco & Fedele, ).…”
Section: Discussionmentioning
confidence: 99%
“…Because of the relative stability of miRNA expression, some studies have used miRNAs as biomarkers [28]. Recent studies have found that miR-495 was involved in the tumorigenesis and progression of various cancers, including lung cancer [11], nasopharyngeal carcinoma [29], osteosarcoma [30], and melanoma [31]. All of these studies have identified miR-495 as a tumor suppressor.…”
Section: Il-11 Rescues the Inhibition Of Cell Proliferation Mediated mentioning
confidence: 99%
“…The main treatments for NSCLC are surgery, radiotherapy, and chemotherapy, but the efficacy is limited for advanced stages [10]. In addition, the molecular mechanisms underlying NSCLC development have yet to be fully elucidated [11]. The exploration of molecular mechanism may help develop targeted therapy, a new treatment option for advanced NSCLC, which can not only improve treatment efficacy but also reduce some adverse effects [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation